The new wine country cookbook : recipes from California's Central Coast - Binns, Brigit Legere (Andrews McMeel Publishing, LLC, 2013)
The author presents recipes for a variety of dishes that use and complement the wines and foods from area of the Pacific Coast running from Monterey to Santa-Barbara, known as California's Central Coast wine country --